O4 Sequential simulation: a new approach to sharing challenges, opportunities and learning in maternity service delivery. (5th November 2017) - Kronfli, Miranda; Weldon, SM; Kneebone, R; Bello, F
Abstract : Background: A recent CQC inspection identified disparities in care quality across maternity services in several London 1 districts, revealing a need to identify challenges and solutions and to share learning across sites. Sequential Simulation 2 (SqS) uses physical simulation to portray selected snapshots from a pathway of care, for pedagogical and engagement activities. In representing the lived experience of service users, SqS provides a platform for facilitated discussion among a diverse range of multidisciplinary participants. SqS workshops at six maternity sites in London aimed to explore service delivery challenges with front-line staff, in order to identify possible solutions, establish whether findings could inform learning outcomes for an educational intervention, and identify unanticipated outcomes of facilitated discussions. Project Description: A collaboratively designed SqS workshop was delivered at each site between January and April 2017. One pilot event was undertaken with service users (November 2016), to incorporate their perspectives into the SqS design. Each comprised a forty-minute simulation of an antenatal pathway, followed by a sixty-minute facilitated discussion amongst the audience participants. Quantitative and qualitative data were collected through post-workshop questionnaires and video-recordings of simulations and the subsequent discussions. Data analysis is ongoing and will be completed in June 2017. Thematic analysis will be undertaken of the facilitated discussion data. Descriptive statistics will be used to analyse the Likert scale questionnaire data. Results: The workshops were attended by 94 participants in total, including 49 midwives (52%), 24 doctors (26%), 7 sonographers (7%), 1 Doula (1%), 1 GP (1%), 1 Service User (1%), 1 Actor (1%), 10 Unknown discipline (11%). 93 questionnaires were completed (99% response rate). Preliminary questionnaire results indicate high levels of participant satisfaction with workshops. Early anecdotal evidence reveals several themes emerging from discussions, including: continuity of health care professional; consistency of advice; information needs; challenges in care delivery; and resource constraints. Some themes were common across sites and some unique to certain sites. Formal results will be included in the oral presentation. Conclusions: Engagement with frontline staff at SqS workshops provided insights into challenges, solutions and potential educational objectives for maternity services in NWL. This information will be valuable in several ways: supporting work of stakeholders such as HEE developing educational strategies for improved quality of care; supporting Trust clinical and education leads seeking buy-in for service reconfiguration and education initiatives; adding to the body of research regarding approaches which support engagement with front-line staff in challenging areas of service delivery. References: . Care Quality Commission. North West London hospitals NHS trust quality report 2014. Accessed on 3rd October, 2015 at: http://www.cqc.org.uk/sites/default/files/new_reports/AAAA1830.pdf . Weldon S-M, Kneebone R, Bello F. Collaborative healthcare remodelling through sequential simulation: A patient and front-line staff perspective. BMJ Simulation and Technology Enhanced Learning 2016;2:78–86.